Characterization of corn-starch edible film with the addition of microalgae extract Chlorella vulgaris as an antioxidant applied to dodol (glutinous-rice cake) products - Ni Wayan Sri Agustini; Kusmiati Kusmiati; Rahmania Admirasari; Dian Alfian Nurcahyanto; Noor Hidhayati; Marsiti Apriastini; Fifi Afiati; Dody Priadi; Baiq Mirna Fitriani; Yelin Adalina; Riza Zainuddin Ahmad (Case Studies in Chemical and Environmental Engineering, 2023)
Dodol, an Indonesian glutinous rice cake, is normally only lasts up to 7 days in room temperature and susceptible to rancidity. Addition of C.vulgaris extract to the edible film used as packaging for dodol is expected to be a new alternative to extend the shelf life of dodol through its antioxidant activity. The aims of this study were to evaluate the characteristics of edible film that added with C.vulgaris extract and to observe people preference, based on its organoleptic parameters. The test was conducted based on different concentrations of corn starch (1%, 3%, and 5%) and different types of solvents used to extract the microalga (ethanol and distilled water). Based on its appearance, aroma, flavor, and texture, dodol with additional C.vulgaris extract in distilled water (J1P1) showed the highest total organoleptic value of 25,87. This is supported by the characteristics of such edible film which has the highest solubility and the highest WVTR values, which were 29,25% and 1,1785, respectively, as well as low peroxide number, compared to that without additional C.vulgaris. These values exhibit no harmful effect to the environment, low risk of rancidity, and longer shelf-life time of dodol.